6th International Conference on Higher Education Advances (HEAd'20) 2020
DOI: 10.4995/head20.2020.10960
|View full text |Cite
|
Sign up to set email alerts
|

Escape room in education: a bibliometric study

Abstract: The impact of technologies in all areas is one of the main points that characterize the current society. In the educational context, recently, great efforts are being made to adapt the system to characteristics and needs of the students of the 21st century. Gamification in education consist on the use of structures, characteristics, dynamics and aesthetics of games for educational purposes, to increase students participation and motivation. The escape room is a gamified activity in which one or more teams must… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…These games are on the rise in the education arena because several studies have reported increased academic performance and knowledge acquisition (Brusi & Cornellà, 2020;Sánchez Lamas, 2018). Gamification is a blanket term used to refer to playfulness in non-game contexts, such as education (Contreras Espinosa, 2016;Manzano-León, Camacho-Lazarraga, et al, 2021;O'Brien & Pitera, 2019;Rutledge et al, 2018;Subhash & Cudney, 2018;Suelves et al, 2020) with clear learning objectives to pursue less traditional forms of teaching and learning that engage learners in the learning process. For instance, a study by Carrión Candel et al (2021) analysed the effectiveness of gamification strategies in a CLIL context, where both content and a foreign language are practised simultaneously (Coyle et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…These games are on the rise in the education arena because several studies have reported increased academic performance and knowledge acquisition (Brusi & Cornellà, 2020;Sánchez Lamas, 2018). Gamification is a blanket term used to refer to playfulness in non-game contexts, such as education (Contreras Espinosa, 2016;Manzano-León, Camacho-Lazarraga, et al, 2021;O'Brien & Pitera, 2019;Rutledge et al, 2018;Subhash & Cudney, 2018;Suelves et al, 2020) with clear learning objectives to pursue less traditional forms of teaching and learning that engage learners in the learning process. For instance, a study by Carrión Candel et al (2021) analysed the effectiveness of gamification strategies in a CLIL context, where both content and a foreign language are practised simultaneously (Coyle et al, 2010).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The EFL classroom, and more broadly, education in general, have traditionally been considered a non-game context (Contreras Espinosa, 2016;Manzano-León, Camacho-Lazarraga, et al, 2021;Rutledge et al, 2018;Suelves et al, 2020). Nevertheless, game-based learning practices have been picking up speed in the last two decades, especially those approaches adopting the use ICTs to transmit moral and social values (Bellés-Calvera, 2018;Bellés-Calvera & Bellés-Fortuño, 2018;Bellés-Fortuño & Bellés-Calvera, 2017;Bellés-Fortuño & Martínez-Hernández, 2019, 2020Clarke et al, 2017;Dichev et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations